Assistive Technology to Support Medical Professionals for Disaster Management - Debrina Kusuma Devi; Rika Yuliwulandari; Zulfan Febriawan; Rifda El Mahroos; Hafiz Tareq Abdullah Khan (Journal of Public Health Sciences, 2026)
Medical assistive technology plays a crucial role in enhancing response and recovery efforts during disasters. This technology includes advanced tools and devices designed to support medical professionals in assessing, treating, and managing patients in high-pressure disaster situations. This paper will explore the medical assistive technology to enhance disaster management. This literature review was conducted via searching in databases such as PubMed, Science Direct, Google Scholar, and Scopus using keywords such as “technology for disaster management”; “pharmaceutical technology for disaster”; “health information”; “communication and technology”; and “disaster medicine technology, robotic, and IoT for healthcare”. The result showed that several tools and software were developed in many countries such as 3D printing for pharmaceuticals for medication printing, drone technology for delivering medical equipment, drugs, and blood, Emergency Medical Information Systems (EMIS), virtual reality (VR) for disaster medicine training, robotics, and innovative mobile applications like SaveMyLife, mental health applications, and rapid DNA technology for disaster victim identification. Using the Health System Resilience Framework, this study highlights how these technologies strengthen service delivery, workforce capacity, and information systems in emergencies. Despite their benefits, most innovations originate in high-income countries, raising challenges for equitable adoption. Future research should address scalability, local adaptation, and ethical considerations to enhance health system resilience in low-resource settings.